2014
DOI: 10.1155/2014/956901
|View full text |Cite
|
Sign up to set email alerts
|

High HPV Infection Prevalence in Men from Infertile Couples and Lack of Relationship between Seminal HPV Infection and Sperm Quality

Abstract: Human papillomaviruses (HPV) are the most frequently sexually transmitted viruses and etiological agents of several human cancers. Controversial results of the role of HPV in infertile population on sperm parameters have been published. The aim of this study was to estimate the type-specific prevalence of HPV DNA infection of the external genitalia and semen in 340 Slovenian men from infertile couples and to establish the relationship between seminal HPV DNA infection and abnormal sperm parameters. Self-taken … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
44
3
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 41 publications
(55 citation statements)
references
References 42 publications
5
44
3
3
Order By: Relevance
“…Human papillomavirus DNA in semen might originate from a male genital tract reservoir or could be a result of contamination of HPV from the skin/mucosa during ejaculation. In agreement with the results of Golob et al () and Luttmer et al (), the control group in this study showed a high prevalence of HPV DNA on genital skin swabs and in semen, and the concordance of HPV genotypes detected in the two locations was high.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Human papillomavirus DNA in semen might originate from a male genital tract reservoir or could be a result of contamination of HPV from the skin/mucosa during ejaculation. In agreement with the results of Golob et al () and Luttmer et al (), the control group in this study showed a high prevalence of HPV DNA on genital skin swabs and in semen, and the concordance of HPV genotypes detected in the two locations was high.…”
Section: Discussionsupporting
confidence: 93%
“…These prevalence rates of more than 60% having HPV on the genital skin as found in this study are higher than the prevalence rates of ~37% found in infertile Slovenian men referred for fertility treatment (Golob et al, ) and ~34% healthy male volunteers from the Netherlands (Luttmer et al, ). The higher prevalence rates found in this study might be explained by geographical differences.…”
Section: Discussioncontrasting
confidence: 68%
See 2 more Smart Citations
“…One study has reported a relationship between viral infection and reduced motility of spermatozoa, supporting a role for the virus as a cause of idiopathic asthenozoospermia. 25 Another study by Golob et al 26…”
Section: A Debated Point Concerns the Association Between Hpv Infectionmentioning
confidence: 99%